A comparative study on methane adsorption onto various adsorbents including activated carbons, zeolites, MWCNT, and MCM-41. Issue 7 (3rd July 2022) - Oguz Erdogan, Fatma
ABSTRACT: In this study, it was aimed to produce low-cost activated carbons from cornelian cherry stones (CCS) by ultrasound-assisted chemical activation with the use of LiOH, KOH, NaOH, and ZnCl2 . In the study, adsorption capacities of the activated carbon samples for CH4 compared with that of commercially obtained activated carbon (AC), multi-walled carbon nanotubes (MWCNT), mesoporous silica (MCM-41), and various zeolites. BET and t-plot analysis have been used for the characterization of adsorbents with the use of N2 adsorption-desorption data and SEM. In the evaluation of the adsorption data, several isotherm models such as DR, Harkins-Jura, Temkin, Freundlich, and Langmuir have been used. It was observed that activated carbons showed higher CH4 adsorption capacity than commercial mesoporous adsorbents and microporous zeolites. The CH4 adsorption capacity of commercial activated carbon was measured to be 0.939 mmol/g, while the CH4 adsorption capacities of activated carbons obtained with the use of NaOH, KOH, LiOH, and ZnCl2 were found to be 2.455, 1.584, 1.477, and 1.433 mmol/g, respectively. Results showed that activated carbons obtained from CCS with the use of KOH, NaOH, LiOH, and ZnCl2 are effective low-cost adsorbents for CH4 adsorption.